Changes in prognosis of the Danish multiple sclerosis population over time. (December 2022) - Magyari, Melinda; Joensen, Hanna; Kopp, Tine Iskov; Pontieri, Luigi; Koch-Henriksen, Nils
Background: The course of multiple sclerosis (MS) appears to be milder in recent decades. Objective: To investigate how time from onset to disability milestones and how demographic and clinical characteristics have changed through subsequent onset cohorts of patients with MS. Methods: In the nationwide Danish Multiple Sclerosis Registry, we have registered all 13, 562 Danish patients with onset of MS or clinically isolated syndrome from 1996 through 2020. For the analyses of prognosis, we used all cases with relapsing onset ( N = 11, 669). After stratification into 5-year onset cohorts, we computed the hazard ratios for disability endpoints for all cohorts having at least 10 years of follow-up and the oldest 1996–2000 onset cohort as reference. Results: Patients in more recent MS onset cohorts have a shorter diagnostic delay and more of them start disease-modifying treatment within 1 year since diagnosis. The prognosis was better for later onset cohorts. For the 2001–2005 cohort, the hazard ratio for confirmed Expanded Disability Status Scale (EDSS) 4 was 0.85 (95% confidence interval (CI), 0.76–0.95) and for confirmed EDSS 6: 0.76 (95% CI, 0.65–0.88). For the more recent 2006–2010 cohort, the corresponding hazard ratios were 0.70 (95% CI, 0.62–0.79) and 0.60 (95% CI, 0.50–0.71). Conclusion: We observed a considerable improvement of the prognosis in recent onset cohorts of relapsing-onset MS.